Analyst Coverage and the Likelihood of Meeting or Beating Analyst Earnings Forecasts - Huang, Shawn X.; Pereira, Raynolde; Wang, Changjiang (Contemporary Accounting Research, 2017)
Abstract This paper examines the relation between analyst coverage and whether firms meet or beat analyst earnings forecasts. We distinguish between whether a firm's reported quarterly earnings meet (i.e., equal or exceed by one cent) or beat (i.e., exceed by more than one cent) its consensus analyst earnings forecasts. We find a positive relation between analyst coverage and whether a firm meets or beats analyst forecasts. However, the more pronounced relation is that between analyst coverage and meeting analyst forecasts. Also, when we consider exogenous shocks to analyst coverage due to brokerage mergers or closures and conglomerate spinoffs, we continue to find a robust positive relation only between analyst coverage and meeting analyst forecasts. To shed light on the causal relation involved, we examine and find that greater analyst coverage is associated with a significantly larger market reaction to negative earnings surprises. We also document that firms with greater analyst coverage are more likely to guide analyst earnings forecasts downwards. Taken together, our evidence suggests that greater analyst coverage raises the pressure on managers to meet analyst earnings forecasts.